PERANCANGAN SISTEM INFORMASI PENCARIAN KERUSAKAN SEPEDA MOTOR SISTEM ELECTRONIC FUEL IGNATION (EFI) - Muhammad Isnaini; Saut Matedius Situmorang (Smart Education, 2021)
Have researched a sistym information about malfunction problems sitem search motor cycle which the device uses advanced methods of reasoning in expert systems . Troubelshooting on motor cycle generally used manually, by determining the symptoms theoretically derived from the experiences so that a technician and student / student often neglected problem finding time and accuracy in solving the problems of motor cycle with EFI sistem repair problems .The method used is the observation on trouble shooting to EFI sensor sistem and collect data from any symptoms of damage to television later in the evaluation of the raw data is entered into a database to an expert system by utilizing visual basic programming .The results will produce a search expert software system that can damage on EFI sensor sparepart can help the technicians and users of the motor cycle itself to recognize and deal damage that occurs EFI component sistem .